2014
DOI: 10.1111/ppc.12077
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nurse Support for the Introduction of the Cardiometabolic Health Nurse in the Australian Mental Health Sector

Abstract: The findings suggest that nurses see the cardiometabolic health nurse role as a promising initiative for closing gaps in cardiometabolic health care and skilling other nurses in mental health. However, as the majority of variance in cardiometabolic health nurse support was unexplained, more research is urgently needed on factors that explain differences in cardiometabolic health nurse endorsement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Physical healthcare.Adapted PHASe [11] plus new items. N = 643 see 5.Routine practiceNationalPhysical health care was explained by self-reported nurse views on patient health, rights and nurse role ideal (‘nurses should be involved in physical health care’), and organisational factors. The latter may be more important in determining physical health careHappell et al [35] [2012]AustraliaCross-sectional survey. Physical healthcare.Questionnaire domains: 1.Perceived Relative Health; 2.…”
Section: Resultsmentioning
confidence: 99%
“…Physical healthcare.Adapted PHASe [11] plus new items. N = 643 see 5.Routine practiceNationalPhysical health care was explained by self-reported nurse views on patient health, rights and nurse role ideal (‘nurses should be involved in physical health care’), and organisational factors. The latter may be more important in determining physical health careHappell et al [35] [2012]AustraliaCross-sectional survey. Physical healthcare.Questionnaire domains: 1.Perceived Relative Health; 2.…”
Section: Resultsmentioning
confidence: 99%
“…The capacity of such a role to address consumer physical health disparities has been well received by nurses (Happell et al . ; Happell et al . ), particularly following the implementation of a similar role (Happell et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that such a role is well‐supported by nurses in mental health (Happell et al . ; Happell et al . 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A specialist nursing position has been proposed as a potential approach to promoting improved physical health care within mental health services. Positions of this kind, while limited in number, have been evaluated positively (Druss et al ; Happell et al ; McKenna et al ), and the attitudes of nurses from mental health services have been favourable (Happell et al ; Happell et al ), becoming more so following the introduction of a position of this type (Happell et al ). However, at this stage the views and opinions of those most closely affected by the inadequacy in physical health care including carers, have not been canvassed.…”
Section: Discussionmentioning
confidence: 99%